Concurrent and Concordant Anal and Oral Human PapillomaVirus Infections Are Not Associated with Sexual Behavior in At-Risk Males - Francesca Rollo; Alessandra Latini; Maria Benevolo; Amalia Giglio; Eugenia Giuliani; Barbara Pichi; Raul Pellini; Massimo Giuliani; Maria Gabriella Donà (Pathogens, 2021)
Men who have sex with men (MSM) harbor the highest prevalence of anal and oral Human Papillomavirus (HPV) infection, particularly if HIV-infected. We investigated anal and oral HPV infections in HIV-infected and HIV-uninfected MSM, to assess concurrent (HPV detected at both sites, irrespective of the genotypes), and concordant infections (same genotype[s] detected at both sites). Matched anal and oral samples from 161 MSM (85 HIV-infected, and 76 HIV-uninfected) were tested with the Linear Array. Determinants of concurrent and concordant infections were evaluated using logistic regression. Anal infections were 4 to 7 times more frequent than oral infections in both study groups (p < 0.0001). Concurrent infections were not significantly different in HIV-infected (25.9%) and HIV-uninfected MSM (17.1%), p = 0.18. A concordant infection was found in 15 MSM (9.3%). Concordance was for one genotype in 14 individuals and for four genotypes in the remaining subject. In the overall population, only age was independently associated with a concurrent infection (AOR = 3.10, 95% CI: 1.34–7.19 for >39 vs. ≤39 years). None of the parameters of sexual behavior showed independent association with concordant infections. Among MSM, concordant anal and oral HPV infections do not seem to be explained by sexual behavior, but might derive from sequential acquisition by autoinoculation.